Thermodynamic characteristics of deep space: hot hazard control case study in 1010-m-deep mine - Kaipeng Wang (Elsevier, 2021)
Control of heat hazards in deep tunnels is vital to underground safety production. Taking a 1010-m-deep coal mine as an example, this paper revealed the variation characteristics of geo-temperature along the depth direction in plain area and the variation characteristics of country rock temperature along the horizontal direction in deep tunnels and the thermodynamic characteristics of the deep space. Using theoretical analysis, numerical simulations, field tests, etc., a new method for calculating cooling loads of deep tunnels and working faces was studied, and heat release law and calculation method of hot water flowing in open canal were discussed. Based on local resource and meteorological conditions and the condition of limited water inflow, the authors designed and implemented the phase-Ⅰ project and phase-Ⅱ project of hazard control system in the 1010-m-deep tunnels. The results showed that the environmental control temperature dropped to 26 ∼ 29 °C, and the average relative humidity was reduced by 5%–15%, which met the comfort standards of underground workers. The failure rate of underground equipment was reduced by half, the investment and operation cost of the heat hazard control system were small, and good environmental and economic and social benefits were achieved.